Factors Affecting the Asset Growth of Indonesian Shaaria Life Insurance Companies - Muhamad Rizki Karim Amrulloh; Farras Abyan Aziz (Review of Islamic Economics and Finance, 2022)
Purpose – This study aims to provide an overview and analysis of how premiums, claims, and investment results have affected asset growth in Indonesian Sharia life insurance companies from 2015 to 2020.Methodology - In this work, quantitative causality methodologies were used as the research methodology. The Financial Services Authority-registered Sharia life insurance company serves as the study's population (FSA). The method used for sampling in research is by purposive sampling with the number of samples as many as eleven Sharia life insurance companies in Indonesia for 6 years of research.Findings - The dependent variables in this study are asset growth and independent variables in this research are premiums, claims and investment returns. The results showed that premiums affect the growth of assets in the negative direction, claims affect the growth of assets in the negative direction and investment returns positively affect the growth of assets.